Residual effect of potassium fertilizer and biochar on growth and yield of maize in the second season - Wid Widowati; A Astutik; Astri Sumiati; Wahyu Fikrinda (Brawijaya University, 2017)
Application of biochar can increase availability of plant nutrients and yield. A field experiment was conducted on anInceptisol with aim to determineresidual potassium fertilizer and biochar application on growth and yield of maize in the second season. A randomized block design was used with three replication. The treaments were residual application of potassium and biochar that consisted of biochar only (30 t/ha), and biochar plus several levels of potassium apllication (0, 50, 100, 150 and 200 kg/ha), included application of 200 kg/ha potassium without biochar. Basal fertilizersapplied in the first season were 90 kg N/ha and 100 kg P205, and in the second season was 90 kg N/ha. The results showed that residual biochar alone or combined with different levels of potassium application increased yield of maize. Residual biochar increased avalilabilty of N, P, K, Ca, and Na in the soil.